1999
DOI: 10.1346/ccmn.1999.0470304
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of the Smectite to Illite Transformation in Cretaceous Bentonites, Cerro Negro, New Mexico

Abstract: Abstract--The thermal effects, as well as the survivability and origins of microorganisms in Cretaceous rocks, are evaluated from the timing and extent of the smectite to illite transformation in Cretaceous bentonites collected from cores outside the thermal aureole of the Pliocene Cerro Negro volcanic neck. Overall, randomly ordered mixed-layered illite-smectite (I-S) is the predominant clay mineral in these bentonites, and the K-Ar ages of I-S range from 36 to 48 Ma (21 analyses, two additional analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 28 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…This ensured equivalence of the respective portions taken for Ar and K measurements. The measurements were done using procedures such as those of Elliott et al (1999). The amount and isotopic composition of the Ar were determined by mass spectrometry after isotope dilution with 38 Ar.…”
Section: E T H O D Smentioning
confidence: 99%
“…This ensured equivalence of the respective portions taken for Ar and K measurements. The measurements were done using procedures such as those of Elliott et al (1999). The amount and isotopic composition of the Ar were determined by mass spectrometry after isotope dilution with 38 Ar.…”
Section: E T H O D Smentioning
confidence: 99%
“…Their best match produced the values n = 5 (in S n ) and m = 1 (in [K/Na] m ). Elliott et al (1999) also found that the equation of Pytte and Reynolds (1989) with a high order was the best in modeling illitization of bentonite affected by burial, although they expressed their doubts that such equation is the best model for all types of illitization sequences. Altaner (1989) coupled diffusional rates of K in a bentonite bed with illitization rates, in order to model the illite-layer proportion distribution in I-S within the bentonite bed.…”
Section: Type Of Kinetic Equationmentioning
confidence: 99%
“…The reaction has been modeled by several authors using field samples and laboratory experiments to produce kinetic equations. Some of these equations have been tested against the progress of the reaction in sedimentary basins where the several variables could be reasonably constrained (Pytte and Reynolds, 1989;Elliott et al, 1991;Velde and Vasseur, 1992;Huang et al, 1993;Hillier et al, 1995;Elliott and Matisoff, 1996;Elliott et al, 1999), with the result that none of the kinetic equations has been found to be consistently superior to the others. Hence, the search for the equation governing the rate of smectite illitization is still open.…”
Section: Introductionmentioning
confidence: 99%
“…This mixed-layer clay has two possible sources: (i) it could be recycled from old mudrocks within the Chinle Basin (i.e. the Moenkopi Formation); or (ii) it could be the result of low temperature diagenetic weathering of volcanic ash (Srodon, 1984;Inoue et al, 1990;Cuadros & Altaner, 1998;Elliott et al, 1999).…”
Section: Matrixmentioning
confidence: 99%